Gems from Genesis - Chambers, Oswald 1874-1917 (Worcester, UK Oswald Chambers Publications Association, 1989)
Contents : Our portrait in Genesis, c.1957, OCPA ; Not knowing whither, c. 1934, OCPA.
Keywords: Bible. O.T. Genesis -- devotional literature